Could hormonal and follicular rearrangements explain timely menopause in unilaterally oophorectomized women?. Issue 7 (25th May 2021) - Grynberg, M; Labrosse, J; Bennani Smires, B; Sifer, C; Peigne, M; Sonigo, C
Abstract: STUDY QUESTION: Does unilateral oophorectomy modify the relationship between serum anti-Müllerian hormone (AMH) levels and antral follicle count (AFC)? SUMMARY ANSWER: No altered 'per-ovary' and 'per-follicle' AMH production and antral follicle distribution was evident in unilaterally oophorectomized women compared to matched controls. WHAT IS KNOWN ALREADY: The age of menopause onset is relatively unchanged in patients having undergone unilateral oophorectomy. Mechanisms that occur to preserve and maintain ovarian function in this context remain to be elucidated. STUDY DESIGN, SIZE, DURATION: Forty-one infertile women, with no polycystic ovary syndrome (PCOS) and no endometriosis, aged 19–42 years old, having undergone unilateral oophorectomy (One Ovary group; average time since surgery: 23.8 ± 2.2 months) were retrospectively age-matched (±1 year) with 205 infertile women having two intact ovaries and similar clinical features (Control group). PARTICIPANTS/MATERIALS, SETTING, METHODS: Serum AMH levels, 3–4 mm AFC, 5–12 mm AFC, and total AFC (3–12 mm) were assessed on cycle Day 3 in both groups. Hormonal and ultrasonographic measurements obtained from patients in the Control group (i.e. having two ovaries) were divided by two to be compared with measurements obtained from patients of the One Ovary group (i.e. having one single remaining ovary). To estimate per-follicle AMH production, we calculated the ratio between serum AMH levels over 3–4 mm AFC, 5–12 mm AFC, and total AFC (3–12 mm), and the strength of the correlation between serum AMH levels and total AFC. The main outcome measure was to assess Day 3 AMH/Day 3 AFC ratio and hormonal-follicular correlation. MAIN RESULTS AND THE ROLE OF CHANCE: As expected, before correction, mean serum AMH levels (1.46 ± 0.2 vs 2.77 ± 0.1 ng/ml, P < 0.001) and total AFC (7.3 ± 0.6 vs 15.1 ± 0.4 follicles, P < 0.0001) were lower in the One Ovary group compared to the Control group, respectively. Yet, after correction, per-ovary AMH levels (1.46 ± 0.2 vs 1.39 ± 0.1 ng/ml) and total AFC (7.3 ± 0.6 vs 7.5 ± 0.2 follicles) values were comparable between the two groups. Consistently, per-follicle AMH levels (3–4 mm, 5–12 mm, and total) were not significantly different between the two groups (0.39 ± 0.05 vs 0.37 ± 0.02 ng/ml/follicle; 0.69 ± 0.12 vs 0.59 ± 0.05 ng/ml/follicle, and 0.23 ± 0.03 vs 0.19 ± 0.01 ng/ml/follicle; respectively). In addition, the prevalence of 3–4 mm follicles was comparable between the two groups (66.7% for One Ovary group vs 58.8% for Control group, respectively). Finally, the correlation between serum AMH levels and total AFC was similar for patients in the One Ovary group (r = 0.70; P < 0.0001) compared to those in the Control group (r = 0.68; P < 0.0001). LIMITATIONS/REASONS FOR CAUTION: The retrospective character of the analysis might lead to potential bias. WIDER IMPLICATIONS OF THE FINDINGS: The present investigation did not provide evidence of altered 'per-ovary' and 'per-follicle' AMH production and antral follicle distribution in unilaterally oophorectomized women compared to matched controls. Further studies are warranted to support the hypothesis that follicle-sparing mechanisms are clearly at stake in remaining ovaries after unilateral oophorectomy to explain their long-lasting function and timely menopausal onset. STUDY FUNDING/COMPETING INTEREST(S): The authors have no funding or competing interests to declare. TRIAL REGISTRATION NUMBER: N/A.